Thyroid Carcinoma on the Side of the Absent Lobe in a Patient with Thyroid Hemiagenesis - Hiroki Sato; Kiyoaki Tsukahara; Ray Motohashi; Midori Wakiya; Hiromi Serizawa; Atsushi Kurata (Case Reports in Otolaryngology)
Background. Thyroid carcinoma complicated by hemiagenesis is very rare, and previous reports have not described this cancer on the side of the absent lobe. Methods and Results. We report the case of a 64-year-old woman in whom left thyroid hemiagenesis was discovered incidentally during investigations of abnormal sensation during swallowing. A tumorous 1.4 cm lesion was also found on the side of the absent lobe, left of the isthmus. Fine-needle aspiration biopsy revealed class V papillary carcinoma, but no lymph node metastases. Total thyroidectomy was performed for stage cT1bN0M0 carcinoma. Histopathology revealed normal thyroid tissues in the right lobe and isthmus, while the left lobe was absent. The mostly papillary carcinoma was adjacent to the truncated thyroid tissue, with a portion histologically consistent with poorly differentiated carcinoma. Conclusions. All previously reported cases of thyroid cancer complicated by hemiagenesis have represented carcinoma occurring within the present lobe. This case is extremely rare.